The Conservation of VIT1-Dependent Iron Distribution in Seeds - Eroglu, Seckin; Karaca, Nur; Vogel-Mikus, Katarina; Kavčič, Anja; Filiz, Ertugrul; Tanyolac, Bahattin (Frontiers in Plant Science, 2019)
One third of people suffer from anemia, with iron (Fe) deficiency being the most common reason. The human diet includes seeds of staple crops, which contain Fe that is poorly bioavailable. One reason for low bioavailability is that these seeds store Fe in cellular compartments that also contain antinutrients, such as phytate. Thus, several studies have focused on decreasing phytate concentrations. In theory, as an alternative approach, Fe reserves might be directed to cellular compartments that are free of phytate, such as plastids. However, it is not known if seed plastid can represent a major Fe storage compartment in nature. To discover distinct types of Fe storage in nature, we investigated metal localizations in the seeds of more than twenty species using histochemical or X-ray based techniques. Results showed that in Rosids, the largest clade of eudicots, Fe reserves were primarily confined to the embryo of the seeds. Furthermore, inside the embryos, Fe accumulated specifically in the endodermal cell layer, a well-known feature that is mediated by VACUOLAR IRON TRANSPORTER1, VIT1 in model plant Arabidopsis thaliana. In rice, Fe enrichment is lost around the provasculature in the mutants of VIT1 orthologs. Finally, in Carica papaya, Fe accumulated in numerous organelles resembling plastids; however, these organelles accumulated reserve proteins but not ferritin, failing to prove to be plastids. By investigating Fe distribution in distinct plant lineages, this study failed to discover distinct Fe storage patterns that can be useful for biofortification. However, it revealed Fe enrichment is widely conserved in the endodermal cell layer in a VIT1-dependent manner in the plant kingdom.